2005
DOI: 10.2146/ajhp040343
|View full text |Cite
|
Sign up to set email alerts
|

Goal attainment in patients referred to a telephone-based dyslipidemia program

Abstract: LDL-C goal-attainment rates increased in patients referred to a telephone-based hyperlipidemia management program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The Mercy Heart Institute' sC DCM program described in this paper was previously shown to improve LDL-C goal attainment for diabetes patients from 23.2% beforet he intervention to 56% after only 6m onths in the program. 14 This 56% rate of LDL-C goal attainment compares with 47% in the present study.…”
Section: ■■ Conclusionsupporting
confidence: 48%
See 1 more Smart Citation
“…The Mercy Heart Institute' sC DCM program described in this paper was previously shown to improve LDL-C goal attainment for diabetes patients from 23.2% beforet he intervention to 56% after only 6m onths in the program. 14 This 56% rate of LDL-C goal attainment compares with 47% in the present study.…”
Section: ■■ Conclusionsupporting
confidence: 48%
“…Results of other studies on the effectiveness of team-based lipid management have also shown high LDL-C lab testing rates (96.7%-97.3%) and LDL-C <100 mg per dL goal attainment (56.5%-83.3%) in lipid management. [13][14][15] Limitations of those studies include no patient randomization, no comparator-control group, and no evaluation of end point outcomes such as morbidity or mortality.T his is the first study to pair the clinical results of team-based CDCM with emerging P4P initiatives showing both improved quality reporting and potential increased revenue for the medical group.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…Despite the adoption of the national cholesterol education program (NCEP) guidelines, our study shows that patients were more likely to improve their lipid levels and attain their treatment goals when managed with pharmacist intervention than with usual medical practice. Reduction of cholesterol levels have been reported in patients receiving pharmaceutical care (8,(20)(21)(22)(23)(24). Peterson et al reported that a 7-month pharmacist-conducted educational and monitoring programme resulted in cholesterol levels being controlled to below 4AE0 mmol ⁄ L in 44% of the 39 patients in their intervention group compared with 24% of 42 patients in their control (P = 0AE06) (21).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the adoption of the national cholesterol education program (NCEP) guidelines, our study shows that patients were more likely to improve their lipid levels and attain their treatment goals when managed with pharmacist intervention than with usual medical practice. Reduction of cholesterol levels have been reported in patients receiving pharmaceutical care (8, 20–24). Peterson et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation